COMPARISON OF PLEA BARGAINING IN THE UNITED STATES WITH “SPECIAL LINE” IN THE DRAFT BOOK OF CRIMINAL PROCEDURE CODE (KUHAP) IN INDONESIA - Amelia Putrina Lumbantobing; Sudirman Sitepu; Herlambang (Universitas Bengkulu, 2023)
Plea Bargaining is a faster and more efficient way of resolving criminal cases, where if the Defendant has admitted guilt, the Defendant or his attorney can make an agreement with the public prosecutor regarding the form of indictment and a lighter sentence. Plea Bargaining is widely embraced by Common Law countries. However, in its development, the success of the United States in reducing the pile of cases by using Plea Bargaining has been followed by Civil Law countries such as Germany, France, Russia, Georgia, the Netherlands, Italy, Taiwan. Even in an effort to reform the criminal justice procedural law, Indonesia has also adopted the basic concept of Plea Bargaining into the Draft Criminal Procedure Code with a concept called